O empoderamento do consumidor como caminho para seu bem-estar emocional - Linardi, Marcelo Augusto (2020)
The cognitive and affective self-assessments of a person about their life define the sense of emotional well-being adequately; the experiences of consumption are presented as possibly uncomfortable everyday situations, where the emotional well-being is impacted and sometimes regulated by coping strategies. This study aims to evaluate the roles of consumer empowerment, consumption vulnerability and coping strategies in the individual's emotional well-being. For this purpose, a conceptual model is proposed using four constructs that had their scales translated and adapted to the Portuguese language. This research is the first to relate important constructs of consumer behaviour with the vulnerability in consumption; a survey type research was employed with 269 consumers of fixed or mobile Internet providers; the data were analysed through a model of structural equations, using the partial least square technique. The results showed that consumer vulnerability generates a negative impact on the emotional well-being of the consumer, who seeks in coping strategies a condition to regulate this stressful event; it was also evaluated in this research the relationship of the role of consumer empowerment, which proved to be a robust tool to shield the emotional well-being of the harmful effects of vulnerability in consumption. This research contributes academically with the instrumentalisation of a scale of vulnerability in the Portuguese language, expanding the possibility for new studies on consumer behaviour. From the managerial point of view, it is expected that the results of this study can contribute to improving the understanding of the phenomenon of vulnerability and the potential effect of consumer empowerment so that companies and policymakers can guide their work assertively and in favour of the emotional well-being of consumers.